Does Competition Influence the Financial Soundness of Banks? Evidence from the Indian Banking Sector - Maji, Santi G.; Hazarika, Preeti (Indian Journal of Finance, 2016)
The impact of market competition on banks’ financial soundness or stability is a current debatable issue in the banking literature. There are two contradictory theoretical views relating to this issue. While the competition fragility view states that competition and bank stability is negatively associated, the competition stability view describes this relationship to be positive. Empirically, researchers have also observed mixed results. This paper examined the influence of market competition on the financial soundness of Indian listed commercial banks. For this, 39 banks including both public and private sector banks were taken into consideration for a period from 1999-2013. In this study, we employed the PRH-statistics to measure the degree of competition. For measuring bank soundness, we used return on assets and market to book ratio. The present effort also examined the influence of customer capital on the financial soundness of Indian banks. The study found that Indian banks are working in a monopolistic free market structure and the degree of competition in public sectors banks is more than that of private sector banks. Employing fixed effect regression model and quantile regression model, the study found that the competition is inversely associated with the banks’ financial soundness, which supports the traditional ’competition fragility’ view. Furthermore, the positive impact of customer capital efficiency on bank soundness indicates the importance of maintaining good relations with the customers for enhancing bank performance in a competitive environment.